Karies Gigi Dan Fluoridasi Elastomer - Roedy Budirahardjo (Fakultas Kedokteran Gigi Universitas Jember, 2010)
Fluoride aplication to modul elastomer very important for caries preventive, as effect of carbohydrate, microrganism at orthodontic attachment. Programe of preventive with fluor can decrease demineralization for orthodontic treatment, specially if it been followed with oral hygiene instruction and motivation. Purposed. This review article purposed for give information about relationship caries with elastomer fluoridation . Discused. elastomer fluoridation was aplicated around brecket orthodonti, where fluor expected many bound by apatite hydroxile. It was addition apatite hydroxylecan be changes become fluor apatite, it more resistant to acid. Conclusion. Elastomer fluoridation very important for orthodontc attachment it could be prevent caries.